Technologies for the Extraction, Separation and Purification of polyphenols – A Review - Suwal, Shyam; Marciniak, Alice (Nepal Journal of Biotechnology, 2019)
Polyphenols are high molecular weight, organic molecules mainly found in plant kingdom. They are mostly known for their positive impact on health, specifically for their antioxidant activity. Indeed, they are widely studied for the prevention of multiple diseases such as cancer, inflammatory, cardiovascular and neurodegenerative diseases. Nevertheless, extractions of these growing interest molecules remain challenging using conventional methods such as solvent extraction. That is why recent researches have focused on improving the extraction of polyphenol by using different technologies such as ultrasound, microwave, pressurized liquid, pulsed electric field, supercritical fluid and high hydrostatic pressure. In the current context, the assisted-extraction should demonstrate their potential to improve the extraction efficiency while being cost-effective and with a low environmental impact. To this end, technologies ought to, for instance, increase the solubility of polyphenol and the permeability of the cell wall. Consequently, this review is focused on the use and potential of these technologies to improve polyphenol extractions from plants as well as their purification using various methods. It discusses of the advantages and disadvantages with some examples of all these technologies assisted-extraction in comparison with conventional extraction method as well as purification technology.